A multi-institutional and interdisciplinary approach to the assessment of vulnerability and adaptation to climate change in the Peruvian Central Andes: problems and prospects - Martínez Grimaldo, Alejandra (2008)
A local integrated assessment of the vulnerability and adaptation to climate change in the Mantaro River Basin, located in Peruvian Central Andes, was developed between years 2003 to 2005. In this paper we present some lessons learned during the development of this study, emphasizing the multi-institutional and interdisciplinary efforts, briefly showing the methodological aspects, and pointing out the main problems found.